Science teachers' perceptions towards the challenges of employing educational technology skills in teaching science and their relationship to their motivation - Miqdadi, Elham; Nawafleh, Waleed; Bani-Khair, Baker Mohammad Jamil (International Journal of Innovative Research and Scientific Studies, 2024)
The current study aimed to reveal the science teachers' perceptions of the challenges they face in employing educational technology skills in teaching science and their relationship to their motivation towards teaching. The descriptive survey method was adopted to achieve this study's objectives. Two questionnaires were developed: the first tool measures science teachers' perceptions of the challenges they face in employing educational technology skills in science instruction. It consists of 35 items distributed over four fields using the Likert scale. The second questionnaire measures the science teachers' motivation towards education, consisting of 31 items. The measures were applied to 100 science teachers in the Directorate of Education of the Koura District. The findings showed that science teachers' perceived challenges in employing technology skills in science education were medium. Statistically significant gender differences at the significance level (α=0.05) were found between the means of participants' responses on the measure of the challenge in favor of females. However, no statistically significant differences were attributable to specialization and years of experience. There were statistically considerable gender differences at the significance level (α=0.05) between the participant's responses on the motivation scale in favor of females. There were no statistically significant differences due to specialization or years of experience. However, there was no statistically significant correlation between science teachers' perceptions of the challenges they face in employing educational technology skills and their motivation to teach science.